2015
DOI: 10.1007/s11356-015-5508-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and efficiency of nutrient removal by Salix jiangsuensis J172 for phytoremediation of urban wastewater

Abstract: Willows are a group of versatile tree species that may have multiple environmental applications. In the present study, Salix jiangsuensis J172 plants were grown in the fixed mats as an economic plant-based treatment system to evaluate its potential for removing nutrients in wastewater. Plants grew normally in wastewater compared with those in Hoagland solution. However, wastewater containing a high concentration of chlorine ions was toxic to S. jiangsuensis J172 plants. The plants accumulated large amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Previous studies have found that saplings irrigated with untreated textile wastewater had shorter length and weight [59][60][61]. As far as the Hoagland solution is concerned, studies also endorsed its efficacy in synthesizing bacterial strains that may be helpful in the treatment of different wastewaters and assist in the growth of crop plants [53]. In our work, the Hoagland solution fulfilled the same purpose.…”
Section: Growth Parameters Of Rice Cultivars In Different Hydroponic ...supporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies have found that saplings irrigated with untreated textile wastewater had shorter length and weight [59][60][61]. As far as the Hoagland solution is concerned, studies also endorsed its efficacy in synthesizing bacterial strains that may be helpful in the treatment of different wastewaters and assist in the growth of crop plants [53]. In our work, the Hoagland solution fulfilled the same purpose.…”
Section: Growth Parameters Of Rice Cultivars In Different Hydroponic ...supporting
confidence: 55%
“…Moreover, it was concluded from these readings that the treatment UTDWW has a negative impact, even with the Hoagland solution. This may be due to the presence of toxic compounds in domestic wastewater that overshadowed the benefits of the Hoagland solution [53]. Previous studies have also shown reduction in seedling length (mainly root length) as compared to the control when grown in raw wastewater mixed with the Hoagland solution in a hydroponic system [31,33,[36][37][38][39].…”
Section: Growth Parameters Of Rice Cultivars In Different Hydroponic ...mentioning
confidence: 99%